MERANCANG PEMELAJARAN BERBASIS MULTIPLE INTELLEGENCES; UPAYA MEMAHAMI KEBERAGAMAN KECERDASAN ANAK - Nurkhin, Ahmad; Wahyudi, Muhammad (Lembaran Ilmu Kependidikan, 2008)
This study is intended to review on how to design multiple-intellegences-based learning in primary schools and its relevance with the effort to understand the children’s multiple intellengences. The paper is based on the current condition in the field that most teachers are unable to present effective and ideal teaching. Therefore, it is no wonder that many students are drown in boredom. The methodology employed in this research are literature review, documentation and interview. Designing multile-intellegencie-based learning is actually not difficult and can be applied to complete the concepts of contextual teaching and learning and integrated learning. The multiple-intellegences-based learning will strengthen and empower the children’s intellegences. This teaching model can be used as a constructive effort to be more understanding on various children’ intellegences.   Kata Kunci: pemelajaran, multiple intellegences, kecerdasan